Berberine: Botanical Occurrence, Traditional Uses, Extraction Methods, and Relevance in Cardiovascular, Metabolic, Hepatic, and Renal Disorders - Neag, Maria A.; Mocan, Andrei; Echeverría, Javier; Pop, Raluca M.; Bocsan, Corina I.; Crişan, Gianina; Buzoianu, Anca D. (Frontiers in Pharmacology, 2018)
Berberine-containing plants have been traditionally used in different parts of the world for the treatment of inflammatory disorders, skin diseases, wound healing, reducing fevers, affections of eyes, treatment of tumors, digestive and respiratory diseases, and microbial pathologies. The physico-chemical properties of berberine contribute to the high diversity of extraction and detection methods. Considering its particularities this review will describes the various methods used mentioned in the literature so far with reference to the most important factors influencing the berberine extraction. Further, the common separation and detection methods like thin layer chromatography, high performance liquid chromatography and mass spectrometry will beare discussed in order to give a complex overview of the existing methods. FurthermoreAdditionally, many clinical and experimental studies suggest that berberine has several useful pharmacological properties, such as immunomodulatory, antioxidative, cardioprotective, hepatoprotective and renoprotective effects. This review summarizes the main information about botanical occurrence, traditional uses, extraction methods and pharmacological effects of berberine and berberine containing plants.